2009
DOI: 10.1016/j.ffa.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

On complementary-dual quasi-cyclic codes

Abstract: A linear code C is said to be a complementary-dual code (an LCDThis paper is to identify few classes of LCD quasi-cyclic (QC) codes. A sufficient condition for a ρ-generator QC code C is given under which C is an LCD code. Another sufficient condition is given for maximal 1-generator codes. We provide two necessary and sufficient conditions for a maximal 1-generator QC code C satisfying certain constraints to be an LCD code. It is shown that unlike cyclic codes, a maximal 1-generator index-2 QC code is reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 8 publications
0
53
0
Order By: Relevance
“…Moreover, the [77, 11,32] code attains the current known lower bound on the minimum distance of both QC and linear codes ( [8,16]). Remark 6.1.…”
Section: Binary Qc Codes Of Rate 1/3mentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, the [77, 11,32] code attains the current known lower bound on the minimum distance of both QC and linear codes ( [8,16]). Remark 6.1.…”
Section: Binary Qc Codes Of Rate 1/3mentioning
confidence: 97%
“…To the best of our knowledge only a few LCD QC codes are known, [11]. This link between E(s 2 )-optimal supersaturated designs and LCD QC codes enables us to retrieve those supersaturated designs from [28,30] for which the restrictions of the previous theorem hold, in order to generate new QC codes in the class of LCD QC codes.…”
Section: Theorem 47mentioning
confidence: 99%
See 1 more Smart Citation
“…Esmaeiliand Yari in [9] studied complementary-dual quasi-cyclic codes. Necessary and sufficient conditions for certain classes of quasi-cyclic codes to be LCD codes were obtained [9]. Dougherty, Kim, Ozkaya, Sok and Solé developed a linear programming bound on the largest size of an LCD code of given length and minimum distance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Later, Sendrier showed that LCD codes meet the asymptotic Gilbert-Varshamov bound using the hull dimension spectra of linear codes [16]. In the literature, LCD codes have been studied extensively and many results and properties for LCD cyclic codes were found [6], [7], [10], [14], [19], [13], [20]. In [8], the problem of constructing LCD MDS codes over finite fields of even characteristic was solved.…”
Section: Introductionmentioning
confidence: 99%